Three generations of changing gender patterns of schooling in the People's Republic of China - Kathleen McGarry; Xiaoting Sun (Asian Development Bank Institute (ADBI), 2018)
The phenomenon of son preference in the People's Republic of China and throughout much of Asia has been well documented. However, changing economic conditions, such as increases in educational attainment and employment opportunities for women and the rise in the prevalence of one-child families, have likely changed the incentives for parents to invest in daughters. In this paper we take advantage of data spanning three generations of Chinese families to examine the evolution of educational attainment for boys and girls and importantly the relative levels of schooling of each gender. We also use variation in the timing of compulsory schooling laws and the implementation of the one-child policy to assess the effect of these policy measures on the relative educational levels. We find a substantial narrowing of the gap between the schooling of boys and girls, so much so that girls now have more schooling on average than boys. In addition, public policy initiatives had a larger effect in rural than urban areas.
Keywords: I2; I280; J13; J16; 330; compulsory schooling; one-child policy; gender differences in education; People's Republic of China